Transformasi Digital Tata Kelola Pelayanan Administrasi Desa Menuju Smart Village: Penguatan Kapasitas Aparatur dan Partisipasi Masyarakat di Desa Nania, Kota Ambon - Normawati (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to describe and analyze the digital transformation of administrative service governance in Nania Village, Baguala District, Ambon City, as a stepping stone towards a smart village by strengthening the capacity of civil servants and increasing community participation. The activities were implemented using a participatory approach and community-based service learning design, through the stages of initial mapping, socialization, training, implementation of a simple digital administration system, mentoring, and reflective evaluation. Data were collected through observation, interviews, FGDs, documentation, and questionnaires, then analyzed using simple qualitative and quantitative descriptive methods. The results show a significant increase in the digital capacity of civil servants; approximately 80% of village officials are able to manage population databases and letter archives electronically. The average document processing time has decreased from 3–5 days to 1–2 working days, with clearer, more predictable, and auditable procedures. As many as 75% of respondents stated that services are faster and more transparent, and they are more active in utilizing village digital channels. In addition, there has been a shift in work culture from a personal pattern to a more collaborative and accountable system-based work pattern, so that Nania Village has begun to play a role as an early model for a smart village in Ambon City. These findings confirm that digitizing village administrative services can be an effective strategy for strengthening governance and public trust in coastal/island areas.